Automation of DNA computing readout method based on real-time PCR implemented on DNA engine opticon 2 system - Mohamed Saaid, Muhammad Faiz (2012)
Previously, an automation of a DNA computing readout method for the Hamiltonian Path Problem (HPP) has been implemented based on LightCycler System. In this study, a similar readout approach is implemented based on DNA Engine Opticon 2 System. The readout approach consists of two steps: real-time amplification in vitro using TaqMan-based real-time PCR, followed by an in silico phase. The in silico phase consists of a data clustering algorithm and an information processing to extract the Hamiltonian path after the TaqMan \YES and \NO reactions have been identified. The result indicates that the automation of DNA computing readout method can be efficiently implemented on DNA Engine Opticon 2 System.